Serum and gene expression profile of cytokines following combination of yoga training and vitamin D supplementation in breast cancer survivors: a randomized controlled trial - Mahdi Naderi; Hajar Kordestani; Zahra Sahebi; Vahid Khedmati Zare; Sadegh Amani-Shalamzari; Mojtaba Kaviani; Joachim Wiskemann; Mahdieh Molanouri Shamsi (BMC, 2022)
Abstract Background This study aimed to examine the effect of the combination of yoga training with high vitamin D dose supplementation on the expression and systemic levels of inflammatory cytokines and psychophysical status of breast cancer survivors. Methods Thirty volunteered breast cancer survivors (48 ± 8 years) were randomly allocated to a high dose (4000 IU) of vitamin D supplementation (HD) group (n = 10), yoga with a high dose of vitamin D (YHD) group (n = 10), and yoga with a low dose (2000 IU) of vitamin D (YLD) group (n = 10). Participants performed the Hatha yoga style for 12 weeks, twice a week. Blood samples, quality of life (QoL) questionnaire, and physical performance tests were taken before and after the intervention. Results Body fat percentage (ηp 2 = 0.36), handgrip strength (ηp 2 = 0.41) and QoL indicators include global health (ηp 2 = 0.54), functional scales (ηp 2 = 0.49), and symptoms scales (ηp 2 = 0.50) were significantly improved in the both YHD and YLD groups compared to the HD group (p < 0.05). Also, interleukin-10 (IL-10) levels were markedly increased in the Y-HVD group compared to the Y-LVD and HVD groups. Moreover, there were significant decreases in tumor necrosis factor-α (TNF-α) and interleukin-6 levels in the Y-HVD group after the intervention. The anti-inflammatory index (IL-10/TNF-α) was significantly increased in both the yoga groups (P < 0.05). Conclusion Yoga promotes physical and psychological fitness and, in combination with a high dose of vitamin D, improves the cytokine profile, which can effectively manage the side effects associated with cancer. Trial registration IRCT20210726051993N2. Registration date: 2022/02/27. URL: https://www.irct.ir/trial/62079